The least squares stochastic finite element method in structural stability analysis of steel skeletal structures - Kamiński, Marcin; Szafran, Jacek (Zielona Góra: Uniwersytet Zielonogórski)
The main purpose of this work is to verify the influence of the weighting procedure in the Least Squares Method on the probabilistic moments resulting from the stability analysis of steel skeletal structures. We discuss this issue also in the context of the geometrical nonlinearity appearing in the Stochastic Finite Element Method equations for the stability analysis and preservation of the Gaussian probability density function employed to model the Young modulus of a structural steel in this problem.
Keywords: weighted least squares method; Stochastic Finite Element Method; generalized stochastic perturbation technique; stability problems; steel skeletal structures